(untitled) (Diametros, 2005)
Naturalism is the view that only the so-called Natural World that surrounds us exists and that it is knowable by means of general cognitive tools. This has consequences for epistemology, because it determines what is an object of knowledge (a natural object) and how it comes to be known (either empirically or through a structure built upon the empirical, yet with the exclusion of experience that reaches into a supernatural world). Epistemological naturalism can be either radical (Quine; the reduction of epistemology to cognitive psychology) or moderate, granting a certain autonomy to the theory of knowledge with respect to science. The article defends the second position and shows that it justifies the existence of certain problems whose discussion requires going beyond purely scientific data. Nevertheless, naturalized epistemology in any of its forms is incompatible with transcendentalism.